UNRUH-DEWITT DETECTORS IN THE PRESENCE OF SCALAR SOURCES - Matsas, GEA; Sudarsky, D. (World Scientific Publ Co Pte Ltd, 1994)
We analyze the response of Unruh-DeWitt detectors in the presence of inertial scalar sources. We show that, in general, a detector responds to the corresponding Coulomb field. However, in some cases, pure vacuum contributions can overwhelm the influence of the Coulomb field rendering the effect of the external source on the detector's response arbitrarily small. We revisit in this context the celebrated question of whether uniformly accelerated observers can see the radiation coming from an inertial charge, and point out the present impediments to answering this question.